Development of a model to predict the 10-year cumulative risk of second primary cancer among cancer survivors. (April 2017) - Moitry, Marie; Velten, Michel; Trétarre, Brigitte; Bara, Simona; Daubisse-Marliac, Laetitia; Lapôtre-Ledoux, Bénédicte; Troussard, Xavier; Molinié, Florence; Ligier, Karine; Woronoff, Anne-Sophie; Bouvier, Véronique; Colonna, Marc; et al.
Highlights: We quantified the 10-year cumulative risk of second primary cancer. Depending on first cancer sites, it ranged from 6.2% to 44.0%. Compared with the general population, it was dramatically elevated for tobacco-related cancers. For head and neck first cancers, the increased risk reached +35.6%. This could be an argument to convince patients of the value of lifestyle changes. Abstract: Background: To develop a prediction model to quantify the cumulative risk of Second Primary Cancer (SPC) among cancer patients given that they survive their disease. Methods: A cohort of 293, 435 patients based on data from twelve French cancer registries was analyzed. For five first cancer sites, SPC incidence rates were estimated using Poisson regression models. The cumulative risks of SPC were computed for different follow-up times. For comparison purpose, the same method was used to estimate the probability of cancer in the general population. Results: In this population-based cohort, 27, 320 patients presented with a SPC. The cumulative risk of SPC varied depending on first cancer site, with a 10-year cumulative probability of SPC ranging from 6.2% for women with breast cancer to 44.0% for men with head and neck cancer. Compared with the general population, the 10-year cumulative risk of SPC was dramatically elevated for tobacco-related first cancers, with an increase of +7.3% for men aged 55 to 64 with a first lung cancer and +35.6% for men aged 45 to 54 with a first head and neck cancer. Lower differences were observed among patients diagnosed with a first prostate cancer (+5.5% among men aged 55 to 64), colorectal (+4.1% for women aged 55 to 64 and +6.3% for men aged 55 to 64), and breast (+2.0% among females aged 75 and older) cancers. Conclusion: This study provides physicians with a practical estimate to assess the risk of SPC of their patients more accurately.